2018
DOI: 10.1097/mpg.0000000000001949
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Eosinophilic Esophagitis Is Associated With Increased Lamina Propria Immunoglobulin G4‐Positive Plasma Cells

Abstract: We demonstrate that active esophagitis in pediatric EoE patients is associated with elevated levels of IgG4-positive plasma cells, which was more significant in EoE patients with a documented food allergy. Our study also adds to the growing literature that EoE may involve more than just an exaggerated TH2 immune response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
23
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 19 publications
6
23
1
1
Order By: Relevance
“…15 Pediatric EoE patients with active esophagitis have been shown to be associated with increased levels of IgG4-positive plasma cells, particularly in those with a food allergy. 13 Esophageal IgG4 levels in children have also been found to correlate with peak eosinophil count; mean histologic grade; and esophageal IL4, IL13, and IL10 and had strong associations with a subset of the EoE transcriptome. 16 As our study cohort consists purely of adults, comparisons with the aforementioned studies may not be appropriate as the EoE disease process has been shown to be different in adults and children, with progression from an inflammatory to a fibrostenotic phenotype.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…15 Pediatric EoE patients with active esophagitis have been shown to be associated with increased levels of IgG4-positive plasma cells, particularly in those with a food allergy. 13 Esophageal IgG4 levels in children have also been found to correlate with peak eosinophil count; mean histologic grade; and esophageal IL4, IL13, and IL10 and had strong associations with a subset of the EoE transcriptome. 16 As our study cohort consists purely of adults, comparisons with the aforementioned studies may not be appropriate as the EoE disease process has been shown to be different in adults and children, with progression from an inflammatory to a fibrostenotic phenotype.…”
Section: Discussionmentioning
confidence: 96%
“…Although we confirm that IgG4 stain is significantly more prevalent in EoE than GERD, the specificity is not 100% and is consistent with most previous studies. [11][12][13][14][15][16] In the current study, less than 10% of GERD patients had a positive IgG4 stain, and up to a quarter of EoE patients had a negative IgG4 stain. Overall, our study suggests that the use of IgG4 stain has a positive predictive value of 92% for distinguishing EoE from GERD, which can be valuable in the clinical assessment of undifferentiated presentation.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The presence of multiple foodspecific serum IgE antibodies correlates with esophageal eosinophilia in children with nonspecific gastrointestinal symptoms, which can be useful in stratifying potential EoE patients [56]. Esophageal and plasma food antigen-specific IgG4 antibodies are elevated in EoE [57][58][59][60]. Furthermore, serum epithelial-specific autoantibodies, specifically, antidesmoglein 3 (DSG3) IgG4 and anti-collagen XVII (NC16A) IgG4, are elevated in EoE.…”
Section: Diagnosis Of Eoementioning
confidence: 99%